(untitled) (Orinoquia, 2020)
This was a qualitative study of residents living in the Camilo Torres neighbourhood on the riverbanks of Caño Gramalote in the municipality of Villavicencio, Meta, Colombia; it involved providing illustrative mixed-method examples regarding the properties’ vulnerability and determined the effects of flooding. What was physically observed was crossed with secondary references to determine action taken against events in the area. The “life history” strategy was used for gathering information from which a body of text was constructed for establishing relationships and meaning. This determined that changes in land use along with the containment measures taken by the municipality have led to the increased vulnerability of the population residing there.